Breeding toward improved ecological plant–microbiome interactions. (November 2022) - Nerva, Luca; Sandrini, Marco; Moffa, Loredana; Velasco, Riccardo; Balestrini, Raffaella; Chitarra, Walter
Abstract : Domestication processes, amplified by breeding programs, have allowed the selection of more productive genotypes and more suitable crop lines capable of coping with the changing climate. Notwithstanding these advancements, the impact of plant breeding on the ecology of plant–microbiome interactions has not been adequately considered yet. This includes the possible exploitation of beneficial plant–microbe interactions to develop crops with improved performance and better adaptability to any environmental scenario. Here we discuss the exploitation of customized synthetic microbial communities in agricultural systems to develop more sustainable breeding strategies based on the implementation of multiple interactions between plants and their beneficial associated microorganisms. Highlights: Domestication process and breeding programs, focused exclusively on the selection and improvement of specific plant traits, have negatively affected the recruitment and functionality of beneficial associations in agricultural systems. Rhizosphere and root-associated microorganisms play important roles in plant growth and resilience. Breeding programs aiming to rationally manipulate root traits in order to recruit beneficial microorganisms or to deter pathogens need to be developed. The development and application of synthetic communities ('SynComs') represent a sustainable way to improve plant growth and resilience.